Nationalism Values In Arabic Textbooks: An Analysis Of Indonesian Ministry Of Religious Affairs-Endorsed Arabic Textbooks - Jaeni, Muhamad; Ghufron, M. Ali; Muassomah, Muassomah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Arabic textbooks function as language learning tools and vehicles for instilling nationalist values. This study uses content analysis to examine three Arabic textbooks the Ministry of Religious Affairs endorsed, focusing on representations of nationalism, symbols, and directives within Arabic and local cultural contexts. The findings reveal that the textbooks emphasize fundamental values of nationalism, including patriotism, tolerance, fraternity, and environmental care. Verbal representations highlight a love for Indonesia and religious understanding, while visual representations, such as historical structures and natural scenery, reinforce patriotism, unity, cultural appreciation, and environmental stewardship. Through Arabic language education, students are encouraged to embrace their national identity, foster cross-cultural understanding, and contribute positively to Indonesian society. This study underscores the role of Arabic textbooks in promoting nationalist values and shaping responsible citizens committed to Indonesia's progress and well-being.